Effect of Cefazolin on endometrial cytology and reagent test strips parameters in bovine endometritis - BARAKAT Τ.Μ.; SHAWKY, G.; ABSY, G.; ABD EL-RAHMAN RAGAB, M. (Journal of the Hellenic Veterinary Medical Society, 2021)
Endometritis is one of uterine disorders in dairy cows causing low fertility. This study explored effects of intrauterine (IU) infusion of Cefazolin on endometrial cytology and reagent test strips parameters (leukocyte esterase [LE] and pH) in bovine subclinical endometritis. A total of 90 cows at 49-56 days in milk (DIM) diagnosed for subclinical endometritis were divided randomlyinto three groups, group I (n = 35), treated with IU infusion of 2 grams Cefazolin (Zinol ®, Pharco) diluted with 50 ml saline; group II (n = 28), treated with IU infusion of 2 gramsCephalexin (Ceporex®, GlaxoSmithKline) diluted with 50 ml saline; group III (n = 27), cows kept as untreated control. Cytological examination and reagent test strips were performed in uterine material derived with the cotton swab technique before treatment program and repeated two times later, in 10 days interval. The cows were artificially inseminated at first oestrous after the end of treatment program and conception rates were evaluated. After the end of treatment program, polymorphonuclear cells (PMN) decreased significantly (P <0.05) in Cefazolin and Cephalexin groups (3.23% and 4.39% respectively) compared tocontrol (24.89%) group, also means of LE in these groups became significantly (P<0.05) lower. The Ph value decreased after treatment, this reduction was significant after the first dose of Cefazolin, while in Cephalexin reduction of pH became significant after second dose. Cefazolin had conception rate (77.14%) significantly (P<0.05) higher than cephalexin and control groups (57.14% and 25.93% respectively). Cefazolin and Cephalexin decrease uterine PMN, LE concentration. The pH value after treatment by Cefazolin was lower than in Cephalexin. Moreover, treatment with Cefazolin resulted in a significantly higher conception rate. Thus, Cefazolin is recommended for the treatment of subclinical endometritis in dairy cows.